Enhancement of aerodynamic performance of high speed train through nose profile design: A computational fluid dynamics approach - Mughal, Khurram Hameed; Bugvi, Salman Abubakar; Baig, Basim Tamoor; Ahmad, Taha; Ashraf, Muhammad Irfan; Ahad, Abdul; Abdullah, Ali (Penerbit Universiti Kebangsaan Malaysia, 2022)
Aerodynamic drag of fast-moving train has significant impact on its fuel consumption and design safety. To improve aerodynamic performance, the drag forces on the train surfaces must be reduced. Train’s front-end nose design has boundless geometrical variations that can be applied for improved performance. Three geometric characteristics were used in present research: A-pillar roundness, nose length that controls its shrinking, and nose bluntness. Latin-Hypercube based random sampling method was used to determine appropriate values of these parameters for specific range. Using Computational Fluid Dynamics (CFD), a numerical approach was used to analyze train aerodynamic performance based on selected factors and operating conditions. Comparisons based on analysis of the base design and proposed design models were made and evaluated for enhanced performance. CFD analysis of the base design and iterative improvements in modified designs indicate drag reduction through change in A-pillar roundness and bluntness of nose to be 10% and 22%, respectively. The increase in nose length which controls nose shrinkage causes the drag to increase by 35%. Similarly, the boundary layer and pressure distribution on the front end of train were also considered and analyzed for performance improvement. It was concluded that the length controlling nose shrinkage of proposed train design is the key factor among the selected geometric parameters that has more influence on drag on high-speed train surface in comparison to other parameters considered. This research effort offers a modification, analysis and comparison of front-end nose geometry of high-speed train to improve aerodynamic performance and consequently fuel consumption.